Pengaruh Dukungan Organisasi dan Kepuasan Kerja Terhadap Retensi Karyawan pada PT. Frentax Bisnis Consultindo - Pratama, Maulana Yoga; Jakfar, Jakfar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Employee retention has become a critical issue in human resource management, particularly in organizations facing increasing workforce turnover. This study aims to examine the influence of organizational support and job satisfaction on employee retention at PT. Frentax Bisnis Consultindo. The research adopts a quantitative approach with an associative method. Data were collected using a structured questionnaire distributed to 55 respondents, selected through simple random sampling from a population of 120 employees. Multiple linear regression analysis was employed to test the hypotheses, supported by SPSS version 25. The findings reveal that both organizational support and job satisfaction have a significant positive effect on employee retention, both partially and simultaneously. The regression model demonstrates that a unit increase in organizational support and job satisfaction leads to an increase in retention levels, with an R² value of 0.448. This indicates that 44.8% of the variance in employee retention is explained by the two independent variables, while the remaining 55.2% is influenced by other factors not examined in this study. These results highlight the importance for management to enhance organizational support and job satisfaction as strategic efforts to reduce employee turnover and improve workforce stability.